Relapse during the treatment of pediatric feeding disorders. Issue 3 (22nd March 2022) - Haney, Sarah D.; Greer, Brian D.; Mitteer, Daniel R.; Randall, Kayla R.
Abstract : Resurgence and renewal are treatment‐relapse phenomena in which previously extinguished behavior returns after the conditions for an alternative response worsen or the context changes, respectively. Recently, researchers have evaluated the prevalence of resurgence and renewal when treating destructive behavior with functional communication training. However, resurgence of inappropriate mealtime behavior has yet to be evaluated; perhaps because treatments involve qualitatively different resurgence opportunities (e.g., increased bite‐presentation rate). We evaluated the prevalence of resurgence and renewal of inappropriate mealtime behavior across 22 and 25 applications of extinction‐based treatments, respectively. Resurgence occurred in 41% (9/22) of applications, most often following presentation‐rate increases. Renewal occurred in 52% (13/25) of applications, most often following feeder changes from therapist to caregiver. We discuss these findings in terms of their ability to inform relapse‐mitigation strategies for resurgence and renewal of inappropriate mealtime behavior.